2003
DOI: 10.1073/pnas.1332809100
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of age-related learning deficits and brain oxidative stress in mice with superoxide dismutase/catalase mimetics

Abstract: Oxidative stress has been implicated in cognitive impairment in both old experimental animals and aged humans. This implication has led to the notion that antioxidant defense mechanisms in the brain are not sufficient to prevent age-related increase in oxidative damage and that dietary intake of a variety of antioxidants might be beneficial for preserving brain function. Here we report a dramatic loss of learning and memory function from 8 to 11 months of age in mice, associated with marked increases in severa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
215
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 334 publications
(234 citation statements)
references
References 38 publications
12
215
0
1
Order By: Relevance
“…Extensive evidence exists for lipid peroxidation being an important mechanism of neurodegeneration in the AD (Liu et al, 2003). Prophylactic treatment with nasal administration of quercetin liposomes significantly reversed the impact of oxidative alterations (MDA, SOD, CAT and GPx) seen in Alzheimer's condition induced by AF64A; this shows the antioxidant potential of quercetin liposomes via nasal administration.…”
Section: Discussionmentioning
confidence: 66%
“…Extensive evidence exists for lipid peroxidation being an important mechanism of neurodegeneration in the AD (Liu et al, 2003). Prophylactic treatment with nasal administration of quercetin liposomes significantly reversed the impact of oxidative alterations (MDA, SOD, CAT and GPx) seen in Alzheimer's condition induced by AF64A; this shows the antioxidant potential of quercetin liposomes via nasal administration.…”
Section: Discussionmentioning
confidence: 66%
“…Protein carbonyls (38) were quantitated by derivatization with 2,4-dinitrophenylhydrazine (DNPH) and methionine oxidation determined by the method of Fliss and Brot (39). Tissue was homogenized in 10% wt/volume of 50 mM phosphate buffer, pH 7.4 and centrifuged 10,000 ϫ g for 15 min to remove insoluble debris.…”
Section: Analysis Of 4-hnementioning
confidence: 99%
“…Not surprising therefore that anti-oxidants were intensively tested as potential therapeutic agents against the negative consequences of brain ageing and neurodegenerative disorders [84][85][86]. Generally, it was found that anti-oxidant treatment or activation of anti-oxidative pathways improve brain functions and partially restores age-dependent changes in gene expression both in normal ageing [87,88] and in models of accelerated ageing [89,90]. Clinical data suggest that dietary anti-oxidants have some protective effects against AD, Parkinson's disease and amyotrophic lateral sclerosis [91] and also in pharmacological and genetic models of neurodegenerative disorders [92][93][94].…”
Section: Processes Contributing To Brain Ageingmentioning
confidence: 99%